2018
DOI: 10.1007/s41030-018-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rapid Onset of Action of ICS/LABA Combination Therapies on Respiratory Function in Asthma Patients: A Single-Center, Open-Label, Randomized, Crossover Trial

Abstract: Introduction: Products based on inhaled corticosteroid (ICS)/long-acting b2 agonist (LABA) combinations may provide different clinical benefits. This study was conducted to compare the rapid effects of three such combination products: formoterol/fluticasone (FFC) aerosol (pMDI), formoterol/budesonide (FBC) dry powder inhaler (DPI), and vilanterol/fluticasone furoate (VFC) DPI. Methods: The study design was a three-armed, randomized, crossover study. Patients included in the study had stable moderate asthma, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Consistent with the notion that FP/FORM acts throughout the airways, objective improvements in small airway ventilation heterogeneity (measured using multiple-breath nitrogen washout) have been demonstrated with FP/FORM in patients with normal spirometry characteristics but poor asthma control [30]. Delivery of FP/FORM to the peripheral airways by pMDI and the rapid onset of action after inhalation were also shown to be favorable compared with other ICS/LABA formulations delivered by DPIs [38]. The importance of small airways is increasingly recognized in the control of patients with asthma [40] 2.2.…”
Section: Fp/form Clinical Datamentioning
confidence: 56%
See 1 more Smart Citation
“…Consistent with the notion that FP/FORM acts throughout the airways, objective improvements in small airway ventilation heterogeneity (measured using multiple-breath nitrogen washout) have been demonstrated with FP/FORM in patients with normal spirometry characteristics but poor asthma control [30]. Delivery of FP/FORM to the peripheral airways by pMDI and the rapid onset of action after inhalation were also shown to be favorable compared with other ICS/LABA formulations delivered by DPIs [38]. The importance of small airways is increasingly recognized in the control of patients with asthma [40] 2.2.…”
Section: Fp/form Clinical Datamentioning
confidence: 56%
“…An extensive clinical dataset exists for FP/FORM administered via a pMDI (Table 2) [29][30][31][32][33][34][35][36][37][38]. Furthermore, long-term data from two clinical studies have demonstrated good efficacy, safety, and tolerability with this ICS/LABA combination, including a low rate of exacerbations, over study periods of up to 60 weeks [33,35].…”
Section: Fp/form Clinical Datamentioning
confidence: 99%
“…Moreover, unless the patient uses the device for a certain minimum period and has an opportunity to use another comparable device, the patient will have no basis on which to judge satisfaction or preference with regard to the device used. Different devices also exhibit different patterns of lung deposition, which may significantly affect clinical potency for lung function and individual clinical effects [ 5 , 6 ]. In this study, patient satisfaction and preference were investigated for two of the latest asthma inhalation therapy drugs in Japan: a combination of vilanterol and fluticasone delivered with an Ellipta dry powder inhaler device (VFC Ellipta), and a combination of formoterol and fluticasone delivered with a pressurized metered-dose inhaler device (FFC pMDI).…”
Section: Introductionmentioning
confidence: 99%
“…Different devices exhibit different patterns of lung deposition, which may considerably affect the individual clinical effects [8,9]. Our recent study suggested that different devices for inhaled corticosteroid and long-acting beta agonist (ICS/LABA) combination therapy showed different clinical potency for lung functions [10]. Incorrect usage of inhaler devices may cause insuffi cient drug delivery and hence insuffi cient lung deposition, thereby leading to poor clinical control and worsened adherence of the patient with asthma and COPD.…”
mentioning
confidence: 99%